A novel interleukin-1 receptor-associated kinase 4 from blunt snout bream (Megalobrama amblycephala) is involved in inflammatory response via MyD88-mediated NF-κB signal pathway. Issue 127 (August 2022) - Zhang, Ru; Liu, Yang; Wang, Wenjun; Xu, Yandong; Wang, Zuzhen; Zhong, Huan; Tang, Chenchen; Wang, Jing; Sun, Hongyang; Mao, Haibin; Yan, Jinpeng
Abstract: Interleukin-1 receptor-associated kinase 4 (IRAK4) plays a crucial role in the Toll-like receptor/IL-1R signal pathway, which mediates the downstream signal transduction involved in innate and adaptive immunity. In the present study, an IRAK4 homologue (named as MaIRAK4 ) from blunt snout bream ( Megalobrama amblycephala ) was cloned and characterized. The open reading frame (ORF) of MaIRAK4 contains 1422 nucleotides, encoding a putative protein of 473 amino acids. Protein structural analysis revealed that MaIRAK4 has an N-terminal death domain (DD) and a central kinase domain (S_TKc), similar to those of mammals and other fishes. Multiple sequence alignment demonstrated that MaIRAK4 is highly homologous with that of grass carp (97.67%). The qRT-PCR analysis showed that MaIRAK4 expressed widely in all examined tissues, including heart, liver, spleen, kidney, head-kidney, gill, intestine and muscle, with the highest expression in the liver and spleen. After stimulation with LPS, MaIRAK4 expression upregulated significantly and reached a peak at 6 h and 12 h post LPS stimulation in the spleen and head-kidney, respectively. After challenge with Aeromonas hydrophila, MaIRAK4 expression peaked at 48 h and 72 h in spleen/head-kidney and liver, respectively. These results implied that MaIRAK4 is involved in the host defense against bacterial infection. Subcellular localization analysis indicated that MaIRAK4 distributed in the cytoplasm. Co-immunoprecipitation and subcellular co-localization assay revealed that MaIRAK4 can combine with MaMyD88 through DD domain. MaIRAK4 overexpression can induce slightly the NF-κB promoter activity in HEK 293 cells. However, the activity of NF-κB promoter was dramatically enhanced after co-transfection with MaIRAK4 and MaMyD88 plasmids. The results showed that MaIRAK4 was involved in NF-κB signal pathway mediated by maMyD88 . The expression level of pro-inflammatory cytokines (IL-1β, IL-6, IL-8 and TNF-α) decreased significantly after the siRNA-mediated knockdown of MaIRAK4 . Together, these results suggest that MaIRAK4 plays an important function in the innate immunity of M. amblycephala by inducing cytokines expression. Highlights: An IRAK4 orthologue from blunt snout bream was identified and characterized. MaIRAK4 expression was markedly enhanced after immune stimulations. MaIRAK4 distributed in cytoplasm and co-localized with MaMyD88. MaIRAK4 could directly interact with MaMyD88 through DD domain . MaIRAK4 promotes pro-inflammatory cytokines production via MaMyD88 -mediated NF-κB signaling pathway.